Pengaruh Product Quality, Promotion, dan Islamic Service Quality terhadap Keputusan Pembelian dengan Price sebagai Variabel Moderasi - Rosmayasari, Rosmayasari; Parakkasi, Idris; Katman, Muhammad Nasri (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
One of the problems in the current industrial era is that many foreign companies have emerged which has resulted in competition in the business sector becoming tighter. Thus, entrepreneurs are required to have appropriate business tactics in order to keep their business running and be able to face other competitors. The aim of the research was to determine the relationship between product quality, promotion and Islamic service quality on purchasing decisions at the Annur Shop Bone Store which is moderated by price. This research is quantitative research. The research location was the Annur Shop Bone Shop with a sample of 210 respondents. Sample collection was carried out using purposive sampling technique. Meanwhile, data processing uses the SEM PLS procedure, namely with the help of SmartPLS 4.0.9.5 software. The results of this research state that each variable (product quality, promotion and Islamic service quality) has a positive and significant influence on purchasing decisions. Furthermore, product quality and promotion which are moderated by price also have a positive and significant influence on purchasing decisions. Meanwhile, Islamic service quality moderated by price has a negative and insignificant influence on purchasing decisions at the Annur Shop Bone Store.